Crystal chemistry of Na-rich rectorite from North Little Rock, Arkansas. (2nd January 2018) - Dietel, Jan; Steudel, Annett; Warr, Laurence N.; Emmerich, Katja
Abstract: The rectorite, a regular mixed layer mineral consisting of dioctahedral swelling and non-swelling 2:1 layers, from North Little Rock, Arkansas, was studied to define the crystal chemistry and structural parameters (e.g. layer charge of the different layers, presence of cis/trans-vacancies). X-ray diffraction, simultaneous thermal analysis coupled with mass spectrometry, X-ray fluorescence and cation exchange capacity are used to characterize this rectorite. The rectorite has a coefficient of variation (CV) of 0.19 and a cation exchange capacity of 60 cmol(+)/kg, as determined by the ammonium acetate method. The mineral is best described as a regular interstratification of brammallite-like and highcharged beidellite-like layers. Dehydration occurs at ≈118°C with a mass loss of 6.77% and dehydroxylation occurs in two steps at 470°C and 588°C with an overall mass loss of 4.67%. Peak decomposition of the mass spectrometer curve of evolved water shows ≈20% peak area with a maximum higher than 600°C, indicating ≈20% cis-vacant layers.